2019
DOI: 10.1371/journal.ppat.1008061
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal antibodies against chikungunya virus target multiple distinct epitopes in the E1 and E2 glycoproteins

Abstract: Chikungunya virus (CHIKV) is a mosquito-transmitted alphavirus that causes persistent arthritis in a subset of human patients. We report the isolation and functional characterization of monoclonal antibodies (mAbs) from two patients infected with CHIKV in the Dominican Republic. Single B cell sorting yielded a panel of 46 human mAbs of diverse germline lineages that targeted epitopes within the E1 or E2 glycoproteins. MAbs that recognized either E1 or E2 proteins exhibited neutralizing activity. Viral escape m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…Animal and epidemiological studies have shown that protection from CHIKV disease is associated with the induction of neutralizing antibodies 18 , 24 26 , primarily directed against structural proteins 17 19 . A virus-like particle (VLP) vaccine has reported to induce neutralizing antibodies eight weeks following a homologous prime-boost vaccination 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal and epidemiological studies have shown that protection from CHIKV disease is associated with the induction of neutralizing antibodies 18 , 24 26 , primarily directed against structural proteins 17 19 . A virus-like particle (VLP) vaccine has reported to induce neutralizing antibodies eight weeks following a homologous prime-boost vaccination 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional basis of neutralization by monoclonal antibodies (mAbs) has been previously investigated for several alphaviruses such as arthritogenic CHIKV, RRV and MAYV, and encephalitic VEEV and WEEV [ 44 , 45 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. In the context of EEEV, prior investigations have focused on characterization of immune response to E2 peptides and compared their cross-reactivity to VEEV [ 151 , 152 , 153 , 154 ].…”
Section: Structural Basis Of Eeev Neutralization By Monoclonal Antibodiesmentioning
confidence: 99%
“…If this hypothesis is confirmed, it would suggest that EEEV has likely evolved a means for envelope protein biogenesis while avoiding a deleterious side-effect of glycosylation, i.e., immune detection. Structural basis of EEEV neutralization by monoclonal antibodies: The structural and functional basis of neutralization by monoclonal antibodies (mAbs) has been previously investigated for alphaviruses such as arthritogenic CHIKV, RRV, and, MAYV, and encephalitic VEEV and WEEV [44,45,[132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. In the context of EEEV, prior investigations have focused on characterization of immune response to E2 peptides and compared their cross-reactivity to VEEV [151][152][153][154].…”
Section: Glycosylation Of E1 and E2 Proteins In Eeevmentioning
confidence: 99%